Content and Language Integrated Learning Implementation Through Team Teaching in Biology Lessons: A Quasi-Experimental Design With University Students - Satayev, Malik; Balta, Nuri; Shaymerdenovna, Izbassarova R.; Fernández-Cézar, Raquel; Alcaraz-Mármol, Gema (Frontiers in Education, 2022)
Can engaging university students in Content and Language Integrated Learning (CLIL) increase their achievement in Biology and the English language? The current study explored the effectiveness of team teaching enhanced CLIL on student achievement. Framed in interdisciplinary/cross-curricular teaching, we examined the effect of CLIL strategy on student achievement in a quasi-experimental study with a sample of Biology education students (N = 25) assigned to control and experimental groups. The topic taught through CLIL was the digestive system, and this subject knowledge was used to test the students’ achievement in Biology. Along with the t-test and Mann-Whitney U test a nonparametric ANCOVA was carried out to reveal group differences. We found that engaging in CLIL significantly improved student achievement both in Biology subject knowledge and the English language. We highlight the critical role of CLIL in teaching content and language for science subjects such as Biology at the university level.